Tribological performance of ceramic coatings deposited on polymer substrates - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
In this study, tribological performance of ceramic coatings (Cr2O3, Al2O3TiO2 and ZrO2CaO) deposited on commercial polyethyleneterephthalate have been examined by rubbing Al2O3 balls thereon. The Cr2O3 coating exhibited the greatest hardness and wear resitance in comparison to Al2O3TiO2 and ZrO2CaO coatings. The wear resistance of the coatings increased with increasing hardness.
Keywords: ceramic coatings; polymer; wear